2+5+6x=x+42

Simple and best practice solution for 2+5+6x=x+42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+5+6x=x+42 equation:


Simplifying
2 + 5 + 6x = x + 42

Combine like terms: 2 + 5 = 7
7 + 6x = x + 42

Reorder the terms:
7 + 6x = 42 + x

Solving
7 + 6x = 42 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
7 + 6x + -1x = 42 + x + -1x

Combine like terms: 6x + -1x = 5x
7 + 5x = 42 + x + -1x

Combine like terms: x + -1x = 0
7 + 5x = 42 + 0
7 + 5x = 42

Add '-7' to each side of the equation.
7 + -7 + 5x = 42 + -7

Combine like terms: 7 + -7 = 0
0 + 5x = 42 + -7
5x = 42 + -7

Combine like terms: 42 + -7 = 35
5x = 35

Divide each side by '5'.
x = 7

Simplifying
x = 7

See similar equations:

| x+3/5-7=-2 | | 3/8r=24 | | 2n+14=30 | | x^​4/​(2-​x)^​4=0 | | 2x+3x+9=90 | | x^​4/​(2-​x)^​4 | | 4d-8=4 | | 25+10x=44+21x | | 5*x-7=8 | | 7xy-7y^2-12x=0 | | 6-4x=50 | | x^3+12x^2+9x+27=0 | | 9x/5=-36 | | 2b-10b+b= | | (ab-2a)x=3b-6 | | 8(6-2y)+41=9 | | 7+9x=2x-24 | | (2/3x-1/2)(3x/5-3/4)(4x-1/2)=0 | | 48=3(2x+2) | | x+24-2x=90 | | 13/22-11/26 | | x/3=11.2 | | 6t+3whent=-5 | | x+116.5=180 | | 4z/7-7=10 | | w/2=10 | | 6x+5=-36 | | 45=15+2b | | 10x+21=3x+224 | | -1=3+t | | 2z-9=43 | | (3c^5/2)^4(c^2)^3 |

Equations solver categories